ELICITATION PEDAGOGY: A METHOD OF SECOND LANGUAGE TEACHING IN CHINA - Guo, Maosheng (American journal of semiotics, 1994)
The cramming approach is a shock to many international teachers of English coming to China and has inspired at least two popular books of complaint in the United States, one by Bill Holm (1990) entitled Coming Home Crazy and the other by Sibyl James (1990) called In China with Harpo and Karl. [...]with an increasing contact and exchange between China and the West, greater and greater importance is being placed on foreign language learning policies and practices, especially English. First in the context of interpersonal communication, the teacher plays a leading role and students, under the teacher's guidance, pursue knowledge on their own initiative and with enthusiasm. First of all, I ask some students to write the phrases and sentences on the blackboard in the following order: (1) "... is a review of past research on the topic"; (2) "...lead to some sort of regulations on such foods"; (3) "...will encounter many obstacles in school and on the job"; (4) "What is the effect of ... on ...?"; (5) "place proper emphasis on ..."; and, (6) "make great demands on ..." The typical teacher is confronted with several tens of heads gifted with thinking and mouths inclined to ask questions of various kinds, and above all, vast oceans of knowledge. [...]elicitation teaching is much more difficult than cramming, in which the teacher prepares some items beforehand and merely lectures on them without student interaction.